Consumer acceptance and quality of game meat "droëwors" sausages with different levels of added fat - Bureš, Daniel; Needham, Tersia; Bartoň, Luděk; Lebedová, Nicole; Kotrba, Radim; Řehák, Dalibor; Kučerová, Iva; Klouček, Pavel; Hoffman, Louwrens C (Meat science, 2024)
Droëwors (dried sausage) is a unique dried meat product from South Africa, which is not smoked, fermented, nor is nitrite used in its production. The objective of the study was to compare the quality parameters and consumer acceptance of common eland meat droëwors with different quantities of added beef fat. Three treatments containing either 10, 15, or 20% (by weight) added beef fat were compared regarding chemical composition, fatty acid profiles, and sensory properties. Increasing the amount of fat in the dried product resulted in a significant decrease in the protein and ash percentages. The sausages with 10% added fat had the most favourable fatty acid profile in terms of nutritional value. Several differences were found in the sensory profiles of the products evaluated by the trained sensory panel; in particular, the evaluation scores for texture improved with increasing fat content. No differences were found between the products by the untrained consumer panel for appearance and taste. When the dataset was analysed according to gender, it was found that women evaluated the 10% fat samples more favourably. This is in line with their stated preference for low-fat meat products. For these reasons, the production of sausages with the lowest fat content can be recommended as they best meet consumer expectations.
Keywords: Food Handling; Consumer preference; maso; Fatty Acids; skot; Fat; chování spotřebitelů; Consumer Behavior; Taste; ženské pohlaví; zvířata; Humans; manipulace s potravinami; Dried sausage; masné výrobky; Game meat; Meat; Cattle; Snack food; mastné kyseliny; Antelope; Female; chuť; lidé; Meat Products; Animals